Corynebacterium matruchotii Demography and Adhesion Determinants in the Oral Cavity of Healthy Individuals - Esberg, Anders (Microorganisms, 2020)
Corynebacterium matruchotii may be key in tooth biofilm formation, but information about demographics, bacterial partners, and binding ligands is limited. The aims of this study were to explore C. matruchotii’s demography by age and colonization site (plaque and saliva), in vitro bacterial–bacterial interactions in coaggregation and coadhesion assays, and glycolipids as potential binding ligands in thin-layer chromatogram binding assays. C. matruchotii prevalence increased from 3 months to 18 years old, with 90% and 100% prevalence in saliva and tooth biofilm, respectively. C. matruchotii aggregated in saliva in a dose-dependent manner but lacked the ability to bind to saliva-coated hydroxyapatite. In vivo, C. matruchotii abundance paralleled that of Actinomyces naeslundii, Capnocytophaga sp. HMT 326, Fusobacterium nucleatum subsp. polymorphum, and Tannerella sp. HMT 286. In vitro, C. matruchotii bound both planktonic and surface-bound A. naeslundii, Actinomyces odontolyticus, and F. nucleatum. In addition, C. matruchotii exhibited the ability to bind glycolipids isolated from human erythrocytes (blood group O), human granulocytes, rabbit intestine, human meconium, and rat intestine. Binding assays identified candidate carbohydrate ligands as isoglobotriaosylceramide, Galα3-isoglobotriaosylceramide, lactotriaosylceramide, lactotetraosylceramide, neolactotetraosylceramide, and neolactohexaosylceramide. Thus, C. matruchotii likely uses specific plaque bacteria to adhere to the biofilm and may interact with human tissues through carbohydrate interactions.